Hedging options including transaction costs in incomplete markets - Mher Safarian (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
In this paper we study a hedging problem for European options taking into account the presence of transaction costs. In incomplete markets, i.e. markets without classical restriction, there exists a unique martingale measure. Our approach is based on the Föllmer-Schweizer-Sondermann concept of risk minimizing. In discret time Markov market model we construct a risk minimizing strategy by backwards iteration. The strategy gives a closed-form formula. A continuous time market model using martingale price process shows the existence of a risk minimizing hedging strategy.
urn:nbn:de:swb:90-404138
Keywords: 330; hedging of options; incomplete markets; transaction costs; risk minimization; mean-self strategies